Makna Filosofis Tradisi Baritan Wujud Pelestarian Budaya Jawa Di Desa Pelas Kabupaten Kediri - Dwi, Risna Sagita; Setyawan, Bagus Wahyu (Visual Heritage: Jurnal Kreasi Seni dan Budaya, 2024)
Tradition is an activity and action that is bound by rules that have been determined by customs and religion. One tradition that is still strong and routinely carried out by the Javanese people is the baritan tradition. The meaning of the baritan tradition for the Javanese people is a form of expression of gratitude to God Almighty who has bestowed abundant blessings on crops and also to pray for salvation. The baritan tradition in Pelas village is one of the traditions that is carried out by every community and is carried out at intersections or junctions and prayer rooms with the aim of being a form of gratitude for having been given favors for one year of Islamic or Javanese reckoning and asking for blessings and rejecting logs for the coming year. This study aims to determine the philosophical meaning contained in the baritan tradition in Pelas Village, Kras, Kediri. The research was conducted using qualitative methods in the form of field research with descriptive and phenomenological analysis. Data collection techniques in research using observation and interviews. The object of his research is the baritan tradition in Pelas Village. Based on the research results obtained by the authors, it is known that the philosophical meaning contained in the Baritan tradition includes the meaning of the implementation of the Baritan tradition and the items used when carrying out the Baritan tradition.